Radical Resection of a Late-Relapsed Testicular Germ Cell Tumour: Hepatectomy, Cavotomy, and Thrombectomy - C. Ní Leidhin; C. E. Redmond; A. M. Cahalane; H. M. Heneghan; R. Motyer; E. R. Ryan; E. Hoti (Case Reports in Surgery)
Up to 3.2% of patients with testicular germ cell tumours represent with late-relapsing disease. Aggressive surgical resection confers the greatest chance of cure in this patient group. We present the case of a late and extensively relapsed nonseminomatous germ cell tumour with thrombus present along the entire length of the inferior vena cava, as well as in the right hepatic vein. Techniques practised in liver transplantation were used to achieve complete resection of the tumour thrombus. This case illustrates the enhanced potential for tumour resection through a fusion of principles derived from surgical oncology and liver transplantation.